Daclizumab, a humanised monoclonal antibody to the interleukin 2 receptor (CD25), for the treatment of moderately to severely active ulcerative colitis: a randomised, double blind, placebo controlled, dose ranging trial. Issue 11 (7th April 2006) - Van Assche, G; Sandborn, W J; Feagan, B G; Salzberg, B A; Silvers, D; Monroe, P S; Pandak, W M; Anderson, F H; Valentine, J F; Wild, G E; Geenen, D J; Sprague, R; et al.
Abstract : Background: An uncontrolled pilot study demonstrated that daclizumab, a humanised monoclonal antibody to the interleukin 2 receptor (CD25), might be effective for the treatment of active ulcerative colitis. Methods: A randomised, double blind, placebo controlled trial was conducted to evaluate the efficacy of daclizumab induction therapy in patients with active ulcerative colitis. A total of 159 patients with moderate ulcerative colitis were randomised to receive induction therapy with daclizumab 1 mg/kg intravenously at weeks 0 and 4, or 2 mg/kg intravenously at weeks 0, 2, 4, and 6, or placebo. The primary end point was induction of remission at week 8. Remission was defined as a Mayo score of 0 on both endoscopy and rectal bleeding components and a score of 0 or 1 on stool frequency and physician's global assessment components. Response was defined as a decrease from baseline in the Mayo score of at least 3 points. Results: Two per cent of patients receiving daclizumab 1 mg/kg (p = 0.11 v placebo) and 7% of patients receiving 2 mg/kg (p = 0.73) were in remission at week 8, compared with 10% of those who received placebo. Response occurred at week 8 in 25% of patients receiving daclizumab 1 mg/kg (p = 0.04) and in 33% of patients receiving 2 mg/kg (p = 0.30) versus 44% of those receiving placebo. Daclizumab was well tolerated. The most frequently reported adverse events in daclizumab treated patients compared with placebo treated patients were nasopharyngitis (14.6%) and pyrexia (10.7%). Conclusion: Patients with moderate ulcerative colitis who are treated with daclizumab are not more likely to be in remission or response at eight weeks than patients treated with placebo.